LEGAL CONSEQUENCES ON THE TERMINATION OF BUILDING UTILIZATION RIGHTS WITH THE APPLICATION OF GOVERNMENT REGULATION NUMBER 18 OF 2021 REGARDING MANAGEMENT RIGHTS, LAND RIGHTS, FLAT HOUSING UNITS, AND LAND REGISTRATION - Sunardi, Sunardi; Dewi Navisa, Fitria; Suwanti, Suwanti (Universitas Islam Malang, 2022)
The extension of the Building Use Rights which has expired causes the land rights to be nullified, therefore it is necessary to renew the rights and the imposition of new Mortgage Rights because the Building Use Rights which are used as objects of Mortgage guarantees have a limited time, so of course it will cause legal problems of its own. which will be the subject of discussion in the writing of this thesis. Based on these things, the problems that will be examined in this research are 1. The legal consequences with the expiration of Building Use Rights on mortgages since the enactment of Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration 2 .How the debtor settles his obligations to the right to use the building which has expired to the creditor (bank). 3. What efforts are made by debtors (Banks) to creditors whose guarantees for the Right to Build Certificate have expired. The approach method used is a normative juridical research method where the results of the study can be concluded that. The legal consequences with the expiration of Building Use Rights on mortgages since the enactment of Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and SHGB Land Registrations which expire or HGB expires, change the status of land that was previously attached to the HGB holder to switch to the rightful party in accordance with the initial land status prior to the existence of the Building Use Right, either to the State or to the Management Holder or to the Ownership Right holder. as well as submitting an application for renewal of HGB where with the results of research at the Notary's Office, in the process there must be a letter of approval from the bank where if later the issuance of the SHGB has been completed, the encumbrance of the Mortgage Rights will be immediately submitted. How the Debtor settles his obligations to the right to use the building which has expired to the creditor (Bank). This is by 1. Paying off the debt, increasing land rights by managing the debtor. What efforts are made by debtors (Banks) to creditors whose guarantees for Building Use Rights Certificates have expired can be done in 3 ways, namely: 1. Non-legitimacy a) Rescheduling (re-scheduling) b) Reconditioning (requirements back), c) Restructuring (Rearrangement), 2. Replacement Guarantee 3. Litigation Keywords: SHGB, Mortgage, Settlement